Open Educational Resources for Blended Learning in High Schools: Overcoming Impediments in Developing Countries - Larson, Richard C.; Murray, M. Elizabeth (Journal of Asynchronous Learning Networks, 2008)
With today's computer and telecommunications technologies, every young person can have a quality education regardless of his or her place of birth. This is the dream that Open Educational Resources (OERs), when viewed as a right rather than a privilege, are directed to realize. For developing countries, we propose a type of OER initiative that leverages not only technology but also the skills of the in-class teacher, that utilizes not only the Internet but also lower-tech delivery platforms, and that is created not only by developed countries of the West but also by educators in many countries worldwide. We outline the design of a cross-border, collaborative learning and teaching system called the Blended Learning Open Source Science or Math Studies Initiative (BLOSSOMS), with an associated partnership network established for its implementation in developing countries. BLOSSOMS is to develop a large, free repository of blended-learning video modules for high school math and science classes, created by gifted volunteer educators from around the world and designed to offer potentially transformative learning exercises that will enhance critical thinking skills and retain students' interest in math and science. The initiative has been designed and developed within a multinational network of partner organizations in the developing world, a characteristic that distinguishes it from many other OER projects.
Publisher: Sloan Consortium KerkoCite.ItemAlsoKnownAs: 2339240:5VQ32RRZ 2405685:WN423VFU
Keywords: Asynchronous Communication; Barriers; Blended Learning; Cooperative Programs; Developing Nations; Educational Resources; Educational Technology; High Schools; Instructional Innovation; Learning Modules; Program Development; Shared Resources and Services; Social Networks; Video Technology; ⛔ No DOI found

National Information and Communication Technology Strategy for Education and Training - Ministry of Education, Kenya (2006)
KerkoCite.ItemAlsoKnownAs: 2405685:ZTFFZSKR

E-Learning as Part of Disaster Recovery Planning - Hanssen, Graeme M.; Rana, Tohid Ahmed (2007)
The world has recently witnessed large natural disasters with the Asian tsunami, the Pakistan earthquake, etc, which has resulted in loss of life measured in hundreds of thousands. One or two years later surveys of reconstruction work have revealed less than 25% of schools have been re-established, implicating long term economic and social consequences. Disaster Recovery planning could include rapid deployment of E-learning systems adapted to disaster zones, even with an apparent lack of broadband telecommunications infrastructure. This paper proposes technically innovative solutions to the rapid re-starting of education in disaster-struck communities by introducing the concept of a mobile E-school. Planning for Disaster Recovery could include the solutions proposed herein, as it is also possible to imagine in this Globalization World that budgets of wealthier nations encompassing these concepts. (Contains 1 figure.)
Publication Title: Online Submission KerkoCite.ItemAlsoKnownAs: 2339240:TNQWGH3K 2405685:7VPDA68G
Keywords: Computer Uses in Education; Distance Education; Educational Technology; Emergency Programs; Foreign Countries; Global Approach; Natural Disasters; Online Courses; Telecommunications; Virtual Classrooms

Information and communication technology (ICT) education in the city school, Pakistan - A success story in the large-scale introduction of the UK National Curriculum's ICT component in Pakistan - Ali, I.; Proctor, J. (Aslib Proceedings, 2005)
Purpose - In an age of information technology some developing countries are more vulnerable than others to international competition through failure to utilize fully the benefits of an ICT culture. The authors suggest that the strategies in response must include a radical review of attitudes and methods of delivery of ICT in schools and give as an example the recent experience of The City School, the nationwide schools' organisation in Pakistan with whom they are employed. Design/methodology/approach - The authors review the current position of ICT in schools in Pakistan and suggest as a model of development, for schools of a corresponding standing, that of The City School. They describe how The City School responded to ICT, ensuring that all its pupils would have access to the most modem of ICT courses. Discusses how the decision to implement a complete change, or revolution, in teaching ICT was brought about in a relatively short time. It discusses the nature of the programme, how it was organised, the materials required and the outcomes of its implementation including its outstanding success with pupils and their parents. Findings - The authors chronicle the historical developments within The City School that brought about radical change within a comparatively short period and identify careful planning, training, and the motivation of stakeholders, i.e. pupils, teachers and parents, as key elements in its successful implementation. Originality/value - The authors suggest that The City School experience provides a model that may be emulated by schools elsewhere in both developing and industrially developed countries.
Place: Bradford Publisher: Emerald Group Publishing Limited WOS:000228458000003 KerkoCite.ItemAlsoKnownAs: 10.1108/00012530510589092 2339240:5LZA5PP2 2405685:IZSECS4Z
Keywords: Pakistan; communication technologies; design and development; schools